Water Mass Analysis and End‐Member Mixing Contribution Using Coupled Radiogenic Nd Isotopes and Nd Concentrations: Interaction Between Marginal Seas and the Northwestern Pacific. Issue 5 (8th March 2018) - Che, Hong; Zhang, Jing
Abstract: We analyzed neodymium (Nd) concentrations and isotopic compositions (εNd ) in seawater of the northwestern Pacific marginal seas and adjacent waters. The values of ε Nd in the surface water increase from the Changjiang River Estuary to the outer shelf. This increase in ε Nd from −12.8 to −7.7 is mainly influenced by the terrestrial source and water mixing. Changjiang Diluted Water contributes more than 20% of the volumetric flux in most regions' surface waters during our investigation. The contribution of Kuroshio Subsurface Water to the Changjiang River Estuary is more than 80% in the southern study area. Estimated water contributions from the East China Sea to the northwestern Pacific and the Sea of Japan are approximately 6% and 10%, respectively. These results imply that the East China Sea is a significant source of material to the northwestern Pacific. Key Points: Nd isotopes in the seawater of East China Sea and adjacent Kuroshio area were analyzed The relative contributions of the East China Sea and the North Pacific were estimated using ε Nd The East China Sea is a key material source of the northwestern Pacific Ocean and adjacent marginal seas